Analysis of Telecommunication Industry in the Czech Republic - Schneiderová, Jana; Strouhal, Jiří, 1980-; Hofrichter, Kamil, 1964-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
This thesis deals with development of Telecommunication Industry in The Czech Republic. The first part of the paper captures more complexly overview of global tendencies in the industry. Generally, the key focus is on the last five years from 2009 to 2013 as this was the most dynamic period of the industry so far: new trends such as MVNOs or M2M appeared, telecommunication regulations have tighten up due to united European Union regulations, which all together led to increasing competition in the industry and necessary acquisitions. One of the recent acquisitions -- Telefónica Czech Republic Group and its subsidiaries gained by PPF Group, is analysed in the second part of this thesis through financial analysis. The acquisition's importance and potential benefits are unquestionable as the operator has performed within the last five years that it can react very well during difficult economic and financial times, and it can prosper from its advantages over its main competitors.
Vedoucí práce: Jiří Strouhal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses